(untitled) (ModaPalavra e-periódico, 2012)
The paper aims to understand what was in Gabrielle Chanel that made his name became synonym for elegance and good taste to wear, resisting time and the emergence of numerous stylists and fashion designers. It starts with the study of the brands of products and its analogy with fashion brands, as brands are reflections of the products that they represent and must be suitable to the objectives of the company so they do not disappear from the economic scenario. Next, semiotic is used as an exercise of analysis, which seeks to explain, to describe and understand the signs that made Coco Chanel became a brand continues to instigate people to have a small part of that myth by purchase a product Chanel.